Efficacy and safety of trastuzumab emtansine treatment in patients with metastatic HER-2 positive breast cancer: a single center study - Eyyup Cavdar; Kubilay Karaboyun; Yakup Iriagac; Okan Avci; Erdoğan Selcuk Seber (Iberoamerican Journal of Medicine, 2022)
Introduction: Trastuzumab emtansine (T-DM1) is one of the effective treatment options in human epidermal growth factor receptor 2 (HER2) positive breast cancer patients. In this study, we aimed to find the effect of T-DM1 on survival, its tolerability and prognostic factors of T-DM1 treatment. Material and methods: The study was designed as a single-center, retrospective study that included patients treated in the oncology department of a university hospital in Turkey. HER2-positive patients with metastatic breast cancer who had a progression response to trastuzumab and taxane treatment and received T-DM1 treatment for at least 2 months between 2016-2022 were included in the study. Adverse events were defined according to the Common Terminology Criteria for Adverse Events v5.0 (CTCAE). Kaplan-Meier methodology and Cox proportional hazard modelling were used for survival analyses. Results: The median progression-free survival (mPFS) for T-DM1 was 10.4 months and the median overall survival (mOS) was 22 months. In the created univariate cox regression model, liver metastasis, ECOG performance status, and pre-treatment serum CA 15-3 were found to be factors associated with PFS. Liver metastasis (HR=2.54, p=0.019), ECOG performance status (HR=4.66, p=0.002), and serum CA 15-3 (HR= 2.55, p=0.041) maintained their statistical significance for PFS in the established multivariate analysis. In the regression analysis for OS, only ECOG performance status (HR= 2.61, p=0.023) was found to be prognostic. While toxicity occurred in 46 (82.1%) of the patients, grade 3-4 toxicity developed in 10 (17.9%) patients. The most common side effects were anemia, thrombocytopenia, fatigue and nausea. Conclusions: T-DM1 is a safe and tolerable agent that prolongs survival. Liver metastasis, ECOG performance status, and pre-treatment serum CA 15-3 levels are independent prognostic factors for patients using T-DM1.